Enhancement of Therapeutic Potential of Oncolytic Virus with Homologous Tumor Cell Membranes for Pancreatic Cancer - Wei Chen; Hui Liu; Yue Chen; Meng Gao (IET Nanobiotechnology)
Pancreatic cancer is a leading cause of cancer-related deaths worldwide. Conventional therapies often provide limited success, necessitating the need for novel therapeutic strategies. Oncolytic viruses (OVs) are a class of viruses that specifically target and kill cancer cells while leaving normal cells unharmed. These viruses have shown promise in the treatment of various cancers, including pancreatic cancer. However, their use in clinical settings has been limited by several factors. Their inability to efficiently infect and kill tumor cells. To overcome this limitation, a cell membrane-coated oncolytic virus was developed. However, the necessity of homologous and nonhomologous tumor cell membranes for their function has not yet been proven. This novel virus displayed increased infectivity and killing activity against tumor cells compared to nonhomologous tumor cell membranes and noncoated viruses. We believe that the homologous tumor cell membranes-coated OVs can enhance the therapeutic potential for pancreatic cancer therapy.